(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2024)
The perception of urban and rural environments is multi-dimensional, shaped by the individual preferences of observers, residents, and visitors. Landmarks play a crucial role in the image of a city or rural area, aiding orientation and creating memorable experiences. It enhances navigability, fosters a sense of attachment, and contributes to place identity. Monuments and heritage structures significantly influence the visual ambiance of these environments. The visibility of heritage structures depends on factors such as height, surrounding buildings, skyline, and location. Using Sketch-up software, this paper assesses the visibility of the Rajagopuram in Thiruvasi village, Tamil Nadu. The study evaluates Rajagopuram’s visibility from various distances, concluding that it is a prominent landmark that enhances visual recognition and fosters a strong sense of attachment and place identity. The study underscores the importance of preserving heritage buildings to maintain historical and cultural significance amidst modern changes.